2004
DOI: 10.1116/1.1695333
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preamorphization and recrystallization on indium doping profiles in silicon

Abstract: Articles you may be interested inStudy of millisecond laser annealing on recrystallization, activation, and mobility of laser annealed SOI doped via arsenic ion implantation Fluorine-enhanced boron diffusion in germanium-preamorphized silicon J. Appl. Phys. 98, 073521 (2005); 10.1063/1.2084336 Erbium-implanted silicon-germaniumThe effect of preamorphization and solid-phase epitaxial regrowth on indium doping profiles in silicon has been investigated. It is shown that preamorphized silicon significantly reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Much of the data presented here is a followup to our previous work 13 where we demonstrated that approximately 10% of the indium profile dose was redistributed, in the 10 18 -10 19 cm −3 concentration range, due to recrystallization at 600°C. Much of the data presented here is a followup to our previous work 13 where we demonstrated that approximately 10% of the indium profile dose was redistributed, in the 10 18 -10 19 cm −3 concentration range, due to recrystallization at 600°C.…”
Section: A Correlation With Metastable Solubility: Indium Lead Andsupporting
confidence: 73%
See 1 more Smart Citation
“…Much of the data presented here is a followup to our previous work 13 where we demonstrated that approximately 10% of the indium profile dose was redistributed, in the 10 18 -10 19 cm −3 concentration range, due to recrystallization at 600°C. Much of the data presented here is a followup to our previous work 13 where we demonstrated that approximately 10% of the indium profile dose was redistributed, in the 10 18 -10 19 cm −3 concentration range, due to recrystallization at 600°C.…”
Section: A Correlation With Metastable Solubility: Indium Lead Andsupporting
confidence: 73%
“…In our previous work, 13 indium was observed to redistribute during recrystallization in the 10 18 -10 19 cm −3 concentration range. In our previous work, 13 indium was observed to redistribute during recrystallization in the 10 18 -10 19 cm −3 concentration range.…”
Section: Introductionmentioning
confidence: 81%
“…In non-amorphized regions, the activation of dopants is smaller, and the concentration of point defects is very high. However, several effects related to SPER such as the dopant snow plow effect [27] and diffusion in amorphous Si [28] are ignored.…”
Section: A Recrystallizationmentioning
confidence: 99%
“…Indium profiles after implantation into ~100 nm deep preamorphized Si (black) and after SPER at different temperatures. SIMS results [27] (dashed lines) are compared to simulation results (lines) obtained with Sentaurus Process [4] and the calibrated model for dopant diffusion and redistribution during SPER [18] [25]. During SPER, indium is pushed towards the surface.…”
Section: A Recrystallizationmentioning
confidence: 99%